Relações entre variáveis de: sementes, plântulas, plantas, produção e óleo em mamoneira - Brum, Betânia (2009)
Castor bean is an oil and biodiesel source. Besides, it has a high seed yield potential in the State of Rio Grande do Sul. The objective of this work was to establish the relationship among the variables: seeds, seedlings, adult plants, grain yield and oil quality in two castor bean hybrids. The experiment was conducted at the Federal University of Santa Maria during the 2007/2008 growing season using the hybrids Sara and Lyra. Three plots of each hybrid were sown; each plot was formed by 13 rows with different distances between plants: 0.4, 0.6 and 0.8 m. Before, an evaluation was conducted in regard to individual characteristics of the seeds on a total of 90 seeds for each hybrids. In each plot, the two central rows consisted of 30 plants and these were evaluated from emergence until harvest comprising seedling, adult plant, grain yield and oil quality. In each group of variables the following propositions were tested: multivariate normality, deviation homocedasticity, and linearity in order to analyze the canonical correlations among groups. For the Sara hybrid, the relationships among groups were established mainly by: seeds of higher weight, width and length positively affected seedling vigor; seedlings correlated with longer epicotyls 14 days after emergence (DAE) and longer hipocotyl 7 DAE that were associated with adult plants height at beginning of flowering, average leaf area, average raceme length, average number of capsules per raceme and negatively the raceme average length; higher adult plants at flowering had more capsules per raceme, higher grain yield and lower average raceme length. In regard to the hybrid Lyra, weight and size of seeds did not affect seedling vigor. The relationship among groups was established by: seedlings with longest epicotyls 7 DAE, smallest epicotyls 14 DAE, less degree-days to emergence and greater number of days to emit the first true leaves determined higher number of inflorescences and average leaf area and lower plant height at flowering and degree-days to flowering; adult plants with the higher number of inflorescences positively affected raceme number. Plants of the hybrid Sara presented significant canonical correlations with most of the variables except for oil quality. For the hybrid Lyra, significant canonical correlations were observed only between the variables of seedlings and adult plants; and, between variables of adult plants and grain yield. For the hybrids studied, the oil quality is not determined by the productive variables.